KECELAKAAN KERJA DI AREA PENGEBORAN MINYAK DAN GAS TAHUN 2012 - 2016 - Elien Dwi Septalita (Universitas Airlangga, 2018)
There were 17 accidents at one of drilling area over the past five years. Purpose of this research is to describe how it happened. This research is a descriptive research that used secondary data. The collected data included the number of accidents, the workers who had experience for accident and draft accident investigation at that drilling area for the past five years. The population was the entire workers of this company that recorded as the victims in accidents at the drilling area during 2012 – 2016. The result showed that amount of accident in drilling area was 17 cases with 0.8 Incidence Rate in every 100 labor. The most type of accident was mechanical accident. Then the accidents also happen at the end of the morning shift, it was happened between 14.00-17.59 WIB. And for the accident which has small impact is about 82,35% and for the bigger impact is about 17,65%. The most victims were the workers that had high school graduate. They were ≥ 30 years old. They had work experiences ≥ 5 years. The conclusion of this research is, the trend of accidents is decrease from year to year. In other that, there is still happened 8 of 100 accidents Incidence in that place. .Keywords: accidents, distribution, incidence rate, oil and gas drlling area